Optimization of Automated Real-Time Dashboards - Sasikala, D.; Sharma, K. Venkatesh (Journal of Electronics and Informatics, 2022)
A dashboard is a powerful tool that enables users to verify, analyze, and process all kinds of data. It represents information on a single screen that helps get it just whenever it is essential and achieve the set goals in time. The category of a dashboard varies due to the nature of data they signify and the drive of the corporate they are castoff by. To blueprint a dashboard that will encounter the entire necessities and wholly accomplishing its targets, custom the ideologies of worthy dashboard sketch. But functioning on the project task, continually ponder its objective and the gain of the target spectators. Create it plain, operational, functional and spotlight on mandate demands. Ensure not to agree with the blueprint that complicates customers via the content, besides UI that will require a clear base fitting into the context. Group data, make it consistent, and add custom facets if applicable. Optimize them; finally, get feedback from customers to find out what’s working perfectly and what is to be amended to mark them even happier. In future this optimized dashboard can be blended with Machine Learning, Deep Learning and Artificial Intelligence for amplifying their performance, reducing their cost and time.